A Numerical Study of Jet Propulsion of an Oblate Jellyfish Using a Momentum Exchange-Based Immersed Boundary-Lattice Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2014)
In present paper, the locomotion of an oblate jellyfish is numericallyinvestigated by using a momentum exchange-based immersed boundary-LatticeBoltzmann method based on a dynamic model describing the oblate jellyfish.The present investigation is agreed fairly well with the previous experimentalworks. The Reynolds number and the mass density of the jellyfish are found tohave significant effects on the locomotion of the oblate jellyfish. IncreasingReynolds number, the motion frequency of the jellyfish becomes slow due to thereduced work done for the pulsations, and decreases and increases before andafter the mass density ratio of the jellyfish to the carried fluid is 0.1. Thetotal work increases rapidly at small mass density ratios and slowly increasesto a constant value at large mass density ratio. Moreover, as mass density ratioincreases, the maximum forward velocity significantly reduces in the contractionstage, while the minimum forward velocity increases in the relaxation stage.